GUIDELINES FOR THE SUSTAINABLE MANAGEMENT OF THE FUTURE PROTECTED AREA LIVANJSKO POLJE - Danijela Madžar; Veronika Vlašić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The establishment of protected areas is one of the most effective tools for the preservation of species and natural habitats. Protected areas are crucial for the preservation of ecologically and economically valuable ecosystems and contribute to a better quality of life and well-being of local communities. Planning and proper management of protected areas can help protect the resources needed for the food and water supply of the population and can minimize the impact of climate change. Preservation of biological diversity is a contribution, but also a long-term basis for the sustainable social and economic development of local communities in protected areas. Guided by examples from around the world, Bosnia and Herzegovina wants to protect its naturally and historically valuable areas and in doing so tries to 'reconcile' the economic development of society with the biological values of the area. From this need comes the initiative for the protection of Livanjsko polje, both from the local population and from national and international experts in the field of nature protection. The paper proposes guidelines for the sustainable management of the future protected area Livanjsko polje in accordance with the postulates of sustainable development with the concrete situation and examples available through the published literature. The contribution of the paper is also the wider application of knowledge about the principles of modern protected area management in accordance with the imperative of sustainable development and the assessment of resource use.